2020
DOI: 10.1001/jamanetworkopen.2020.11625
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Deep Learning Model to Identify Lymph Node Metastasis on Magnetic Resonance Imaging in Patients With Cervical Cancer

Abstract: IMPORTANCE Accurate identification of lymph node metastasis preoperatively and noninvasively in patients with cervical cancer can avoid unnecessary surgical intervention and benefit treatment planning. OBJECTIVE To develop a deep learning model using preoperative magnetic resonance imaging for prediction of lymph node metastasis in cervical cancer. DESIGN, SETTING, AND PARTICIPANTS This diagnostic study developed an end-to-end deep learning model to identify lymph node metastasis in cervical cancer using magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 51 publications
3
48
1
Order By: Relevance
“…Transfer learning involves the implementation of a pre-trained network that is further fine-tuned with samples specific to a desired task. Transfer learning has been explored for prediction of lymph node metastasis in patients with cervical cancer using MRI (AUC: 0.9) and breast cancer using CT (AUC: 0.8) with promising results [ 41 , 42 ]. In this work, we used a pretrained VGG model that was originally optimized to classify 1000 types of objects.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer learning involves the implementation of a pre-trained network that is further fine-tuned with samples specific to a desired task. Transfer learning has been explored for prediction of lymph node metastasis in patients with cervical cancer using MRI (AUC: 0.9) and breast cancer using CT (AUC: 0.8) with promising results [ 41 , 42 ]. In this work, we used a pretrained VGG model that was originally optimized to classify 1000 types of objects.…”
Section: Discussionmentioning
confidence: 99%
“…Several CNNs using MRI have been constructed for the diagnosis of uterine tumors to date (19,20). (22), and T2WI + CE-T1WI (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also reported that LNM was not only closely associated with prognosis but also with treatment planning. Patients with LNM may benefit from chemoradiotherapy rather than surgery as their first choice ( Wu et al, 2020 ). Therefore, the diagnosis of LNM in cervical cancer is critical for guiding individualized treatment and avoiding unnecessary surgical intervention.…”
Section: Discussionmentioning
confidence: 99%